RISK FACTORS FOR FIRST SIMPLE FEBRIL ESEIZURES AMONG CHILDREN IN SULAIMANI GOVERNORATE - Abdulatif, Semaa Riyadh; Ghafoor, Ibrahim Khasraw (Journal of Sulaimani Medical College, 2024)
Background Febrile seizures are common problems in children aged between 6-60 months, many studies were conducted on the risk factors associated with the recurrence of simple febrile seizures. However, few research works have been conducted on the risk factors concerning first simple febrile seizures. Objectives To determine the risk factors for the development of first febrile seizure attacks among children in Sulaymani governorate. Patients and Methods A prospective case-control study was conducted at Dr. Jamal Ahmad Rashid Pediatric Teaching Hospital in Sulaymani governorate, during the period from the 1st of April to the 1st of December 2019. A hundred cases (100) diagnosed to have a first attack of simple febrile seizure who had been admitted to the emergency department, were enrolled in our study, and another sex and age-matched 100 children with fever but without seizures, were selected as controls. The age of both groups (cases & controls) ranged from 6 -60 months. A specially designed questionnaire and oral consent were taken during the interview with the parents. Results The study showed that upper respiratory tract infections constituted a major cause of fever among cases, which precipitated febrile seizure (76%) . Significant (,p.value <0.05) association has been noted between the first febrile seizure attack and bottle feeding, prematurity, low birth weight, caesarian section, paternal smoking, as well as family history of febrile seizures has shown a significant value with (P<0.05). Breastfeeding was a protective factor. Conclusion There’s strong association between upper respiratory tract infections in children younger than five years and first attack of simple febrile seizures. Normal vaginal delivery ,breast feeding and avoidance of smoking are protectives for getting simple febrile seizures in susceptible children.
Keywords: febrile seizures; Sulaymani; DrJamal ARashid pediatric hospital